POLA PENDIDIKAN AGAMA DALAM KELUARGA PEKEBUN SAWIT DI DESA SALUKAYU KABUPATEN MAMUJU - Zainuddin Zainuddin; Astifa Sahbaitul Inayah; Safaruddin Safaruddin; Dina Reskiana; Husnul Khatikah (IAI DDI Mangkoso, 2023)
This research is part of the study of Islamic education and family education, which places the family as the primary institution in instilling religious values. The purpose of this study is to analyze the patterns of religious education within the families of oil palm farmers and to identify the challenges and solutions in strengthening it. This study uses a qualitative approach with a case study type. Data collection was carried out through observation, in-depth interviews, and documentation involving oil palm farmers' parents, children, as well as religious and community leaders in Salukayu Village, Papalang District, Mamuju Regency, West Sulawesi Province. The research results show that the pattern of religious education in the families of oil palm farmers is implemented through habituation of worship, parental exemplification, division of roles among family members, and simple and flexible scheduling of children's activities. However, its implementation still faces obstacles such as parents' limited time due to work demands, the scarcity of non-formal religious education institutions, as well as environmental influences and the use of gadgets in children's lives. This study contributes to the development of Islamic education studies by providing a contextual overview of family-based religious education practices in agrarian communities, and emphasizes the importance of synergy between family, society, and religious institutions in sustainably shaping children's religious character.